The Gospel of Luke: Development, Sources, and Conception of God and Jesus | إنجيل لوقا نشأته ومصادره وتصوره للإله وعيسى عليه السلام - Ismail Siddiq (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2021)
This research, which was entitled: (The Gospel of Luke, Its Origin, Sources, and Perception of God and Jesus, Peace be upon Him), deals with the definition of the meaning of the Gospel and an overview of Luke's personality and the origins of his Gospel and its sources. He also stood on the conception of God and Jesus, peace be upon him, in the Bible and the position of the Christians towards it and proved the loss of the original Gospel of Jesus. The researcher concluded with the Qur'an's testimony to the true gospel and his rejection of the current gospel. Perhaps one of the most important reasons for choosing this topic is to find out the state of the current Gospel of Luke and the texts that depict God and Jesus (peace be upon him). And a statement of the most important sources of Luke in this Gospel. Likewise, the Holy Qur’an’s interest in dialogue with the People of the Book, for the Qur’an was filled with dialogue with the People of the Book in many surahs, as God commanded to debate and dialogue with them. Still on pure monotheism. The importance of the topic lies in its usefulness to the People of the Book; And that it confirms and highlights the dominance of the Qur’an over other books and that it is a copyist of them. One of the objectives of this research was to show that the Gospel that the Holy Qur’an talked about is different from the Gospels that the Christians have today. As well as standing on the texts that confirm the humanity of Jesus, peace be upon him, and that he is a prophet and that he is not a son of God or is God, and to achieve the goals that the researcher seeks, he will follow the descriptive analytical approach through the methods of deduction and induction.